Case Report: Dacomitinib May Not Benefit Patients Who Develop Rare Compound Mutations After Later-Line Osimertinib Treatment - Li, Hong-Shuai; Yang, Guang-Jian; Wang, Yan (Frontiers in Oncology, 2021)
The acquired EGFR C797 mutation has been identified as the most notable resistance to osimertinib, and novel secondary mutations of EGFR L718 and L792 residues have also been demonstrated to confer osimertinib resistance, making the choice of medication after osimertinib treatment a quandary. Dacomitinib has been reported to have potential impact on patients acquiring rare compound mutations after osimertinib resistance; however, little evidence is available to date. In five lung adenocarcinoma patients resistant to osimertinib, recurrent mutations at EGFR L792 and/or L718 were identified using targeted next-generation sequencing of tissue or cell-free DNA from plasma or pleural effusion. Dacomitinib was initiated after osimertinib resistance; however, all patients progressed within 2 months. Molecular structural simulation revealed that L792+T790M and L718 mutations could interfere with the binding of dacomitinib to EGFR and potentially cause drug resistance. Our case series study, to our knowledge, is the first to report the clinical efficacy of dacomitinib in this subset of patients.